Contextualisation of Jasser Auda's MaqÄá¹£id SharÄ«'ah on Hysterectomy (Surgical Removal of The Uterus) - Firmansyah , Denny; Sayyaf , R. Tanzil Fawaiq; Bighash , Khadijeh Ahmadi (LPPPM STAI Darul Hikmah Bangkalan, 2023)
Hysterectomy (surgical removal of the uterus) is an alternative method of removing the cervix from a womanâ€™s body through surgery. This action has implications for infertility, so the patient is sentenced to be unable to carry a fetus in the womb forever. Hysterectomy is part of a contemporary problem that requires Islamic legal policies to solve the problem. This article aims to determine the hysterectomy procedure with various backgrounds, causes, and reasons, which are interpreted contextually based on a more comprehensive maqÄá¹£id sharÄ«â€™ah perspective using the theory of a well-known contemporary intellectual figure, namely Jasser Auda. The type of research used refers to library research which is included in the qualitative realm with a descriptive-analytic approach method to produce facts from a particular phenomenon. The results of this study indicate that hysterectomy can be viewed based on context by using the maqÄá¹£id sharÄ«â€™ah system theory according to Jasser Auda through six features, namely Cognitive Nature, Wholeness, Openness, Interrelated Hierarchy, Multidimensionality, and Purposefulness.